"A spectacular irritant": US–Iranian relations during the 1960s and the World's Best Dressed Man. Issue 1 (2nd January 2021) - Offiler, Ben
ABSTRACT: In 1963, the United States Senate Permanent Subcommittee on Investigations received evidence alleging that US aid funds to Iran had been misappropriated and used to bribe prominent American and Iranian figures. Members of the Iranian royal family and high-profile American businessmen and diplomats were implicated in the emerging corruption scandal. The allegations were made by the Iranian businessman and self-proclaimed "World's Best Dressed Man, " Khaibar Khan Gudarzian. While the US Senate would ultimately reject Gudarzian's claims, the scandal amplified tensions between the United States and Iran. American efforts to strengthen ties with the Shah of Iran during the mid-1960s, who was becoming increasingly economically and politically independent, were hampered by the ongoing Gudarzian case. This case study demonstrates the delicate nature of US–Iranian relations and highlights how far the balance of power between the two countries had evolved since the beginning of the decade.